1992
DOI: 10.1104/pp.100.4.1955
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5OH-1,4-Naphthoquinone on Norway Spruce Seeds during Germination

Abstract: The effect of 5-OH-1,4-naphthoquinone (50H-NQ), a known inhibitor of germination and growth and an inducer of oxidative stress, on seeds from Norway spruce (Picea abies) during germination was studied. 50H-NQ was activated by homogenate from seeds to reactive species that reduce oxygen to superoxide radicals in vitro. Increasing concentrations of 50H-NQ increased lipid peroxidation during this activation. Small effects of 50H-NQ on germination of seeds were observed at concentrations up to 200 Mm. However, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Juglone (5‐hydroxy‐1,4‐naphthoquinone) (Table 1) is believed to be released by walnut trees ( Juglans spp) into the soil and accumulate to toxic levels sufficient to limit the growth of competing plants near the trees. Evidence of juglone toxicity comes from: (1) field observation of walnut toxicity toward certain plants causing symptoms collectively referred to as walnut wilt (Dana and Lerner, 1994; Tentinger, 2003); (2) hydroponics‐based solution culture toxicity testing, which demonstrated that juglone is potentially toxic to certain plant species (Funk et al, 1979; Rietveld, 1983; Segura‐Aguilar et al, 1992; Jose and Gillespie, 1998b; Kocacaliskan and Terzi, 2001; Hejl and Koster, 2004); and (3) field evidence of juglone accumulation in soils (Ponder and Tadros, 1985; De Scisciolo et al, 1990; Jose and Gillespie, 1998a). Whether juglone toxicity occurs at the target plant or not depends on its mode of toxic action and whether sufficient juglone concentrations in soil are available to invoke a toxic response.…”
Section: Molecular Properties Of Juglone (5‐hydroxy‐14‐naphthoquinone)mentioning
confidence: 99%
See 2 more Smart Citations
“…Juglone (5‐hydroxy‐1,4‐naphthoquinone) (Table 1) is believed to be released by walnut trees ( Juglans spp) into the soil and accumulate to toxic levels sufficient to limit the growth of competing plants near the trees. Evidence of juglone toxicity comes from: (1) field observation of walnut toxicity toward certain plants causing symptoms collectively referred to as walnut wilt (Dana and Lerner, 1994; Tentinger, 2003); (2) hydroponics‐based solution culture toxicity testing, which demonstrated that juglone is potentially toxic to certain plant species (Funk et al, 1979; Rietveld, 1983; Segura‐Aguilar et al, 1992; Jose and Gillespie, 1998b; Kocacaliskan and Terzi, 2001; Hejl and Koster, 2004); and (3) field evidence of juglone accumulation in soils (Ponder and Tadros, 1985; De Scisciolo et al, 1990; Jose and Gillespie, 1998a). Whether juglone toxicity occurs at the target plant or not depends on its mode of toxic action and whether sufficient juglone concentrations in soil are available to invoke a toxic response.…”
Section: Molecular Properties Of Juglone (5‐hydroxy‐14‐naphthoquinone)mentioning
confidence: 99%
“…In solution culture, Hejl and Koster (2004) reported that juglone interference with maize plants occurred at the roots of target plants by disrupting plasma membrane K + –ATPase activity and associated plant water and nutrient uptake. Some plants appear to have a protective capacity against oxidative stress from juglone by emitting enzymes that metabolize the compound to less toxic hydroquinones (Segura‐Aguilar et al, 1992; Matvienko et al, 2001). Juglone that has been released by source plants into the soil, if not irreversibly sorbed or degraded, will accumulate on soil particles in dynamic equilibrium with the solution phase and serve as an additional pool of juglone for the target plant/organism.…”
Section: Molecular Properties Of Juglone (5‐hydroxy‐14‐naphthoquinone)mentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical responsible for its allelopathy is juglone (5-hydroxy-1, 4 naphthoquinone) (Rice 1974), which has also been isolated from many other plants in the walnut family (Juglandaceae), including Juglans regia (Daglish 1950;Prataviera, Kuniyuki & Ryugo 1983;Ponder & Tadros 1985). This aromatic phytotoxic compound occurs naturally in all parts of the plant, but particularly in leaves and roots (Segura-Aguilar, Hakman & Rydstrom 1992). The plant contains large amounts of nontoxic and colourless hydrojuglone, which is transformed, for example, in the soil after cleavage of the glycosidic bond and oxidation of the aglycone to the toxic and orange juglone (Bertin, Yang & Weston 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Roots, leaves, and hulls contain large quantities of harmless hydrojuglone, which may be oxidized to juglone (Segura-Aguilar et al 1992), then transferred to neighboring plants primarily as a root exudate in the rhizosphere of the black walnut trees (Bertin et al 2003). In susceptible plants, juglone interferes with respiration and photosynthesis (Hejl et al 1993).…”
Section: Introductionmentioning
confidence: 99%